Perancangan User Interface Berbasis Web untuk Home Automation Gateway Berbasis IQRF TR53B - Theresia Wuri Oktaviani (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
One of the easiest ways to minimize electric energy use is by turning off the electrical appliances if they are not being used. Electrical appliances which are generally available in a building are lamps. Lamps control is still using conventional way; that is by using on and off switch. On the other hand, recent technology has invented more modern and sophisticated communication devices that can help people’s life. This research proposes the design of lamps control system that is in the form of web application using PHP programming language that is addressed to end users by pointing at the previous research that has produced a gateway prototype system by using access point. Then, this web application is evaluated by passing through usability testing based on five usability aspects. From the result of the assessment, it could be got reflect time to mean demand 1.332 seconds for turning on and turning off the lamps. The evaluation result of this web application showed that receiving value of usability by the user was above 3 (above the median) using 5 scale or having mean 4 point. Generally, web application that was made had owned usability value; those are good learnability, efficiency, memorability, errors and satisfaction.